Competition issues in the sale of audiovisual rights for major sporting events (UN New YorkUS, 2018)
Highlights the contribution of competition law enforcement to the provision of access by views to broadcast sporting events along with balanced protection for audiovisual rights. Considers international best practices in this area, for reference by developing countries.
Keywords: COMPETITION